ICT in the Application of Language Learning to TESOL in China - Zhang, Hui (Technium Social Sciences Journal, 2021)
Science and technology has become more and more important in education, especially in language teaching and learning. Also, more and more teachers realize it is the popular issue nowadays. In China, the application of ICT in the language class to TESOL has already been a hot topic. This paper is divided into five parts: the first part is the introduction; the second part explains the definition and types of ICT and its advantages in the field of education; the third part describes the basic concepts of TESOL; the fourth part focuses on ICT in the application of language learning to TESOL in China through analyzing the existing problems and underlying causes and providing some suggestion to improve the current situation; the last part is the conclusion. All in all, this paper attempts to contribute to the growing understanding of the present application of ICT in language teaching and learning in China, which will be extremely beneficial for the improvement of the current ICT environment in TESOL, and hopefully offer some references for the future researches in this area.